2013
DOI: 10.1002/ejoc.201300026
|View full text |Cite
|
Sign up to set email alerts
|

Stannylene‐Mediated Regioselective 6‐O‐Glycosylation of Unprotected Phenyl 1‐Thioglycopyranosides

Abstract: A straightforward procedure is described for the synthesis of (1→6)‐linked saccharides by regioselective glycosylation of unprotected glycosyl acceptors. Phenyl 1‐thioglycopyranosides derived from D‐glucose, D‐galactose and D‐mannose were treated with dibutyltin oxide to introduce a stannylene acetal, and then subjected to selective glycosylation at the 6‐position with the Koenigs–Knorr protocol. Peracylated glycosyl bromides of D‐glucose, D‐galactose, D‐mannose and D‐glucosamine were employed as the donors to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Madsen also used dibutyltin oxide in regioselective glycosylation of compound 58 on the unprotected acceptor 57 to form β‐(1–6)‐linked glycoside 59 (Scheme ). The best yield was obtained in the presence of AgOTf and 4Å MS as a desiccant and a very weak acid scavenger.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Madsen also used dibutyltin oxide in regioselective glycosylation of compound 58 on the unprotected acceptor 57 to form β‐(1–6)‐linked glycoside 59 (Scheme ). The best yield was obtained in the presence of AgOTf and 4Å MS as a desiccant and a very weak acid scavenger.…”
Section: Discussionmentioning
confidence: 99%
“…The selectivity for 53 is driven by the selective formation of the tin acetal of 52 at C-2 and C-3, and selective glycosylation at less hindered equatorial C-3 position. In 2003, Kaji [85] also demonstrated that the reactivity of different stannylenes could be influenced by adding a salt such as [86] Madsen [87] also used dibutyltin oxide in regioselective glycosylation of compound 58 on the unprotected acceptor 57 to form -(1-6)-linked glycoside 59 (Scheme 13). The best yield was obtained in the presence of AgOTf and 4Å MS as a desiccant and a very weak acid scavenger.…”
Section: Tin-mediated Glycosylation On Unprotected Acceptorsmentioning
confidence: 99%
“…Attempt to mimic such selectivity remains the grail for glycochemists. Already, regioselective glycosylation of naked acceptors could be performed thanks to transient selective activation of one hydroxyl group against the others using for example dibutyltin­(IV) oxide , or aryl borinic acid , as inducers of regioselectivity. More recently, Taylor and co-workers developed new diarylborinic acid derivatives for the regioselective acylation, alkylation or tosylation of the secondary alcohol of various alkyl glycosides.…”
Section: Introductionmentioning
confidence: 99%
“…A particular challenge would be to glycosylate the secondary alcohols in 2,3,4,6‐unprotected hexopyranosides, and for this reason we decided to explore the use of the cheaper phenylboronic acid as a transient blocking group. As in our recent study with dibutyltin oxide,12a phenyl 1‐thioglycopyranosides were chosen as acceptors, since the products of the regioselective couplings would then be thioglycoside building blocks, which are useful glycosyl donors in oligosaccharide synthesis. Thus, in this paper, we report full details of the regioselective glycosylation of unprotected thiohexopyranosides using an in situ blocking strategy with phenylboronic acid.…”
Section: Introductionmentioning
confidence: 99%